STRATEGI PASANGAN SUAMI ISTRI LONG DISTANCE MARRIAGE DALAM MEMPERTAHANKAN KEUTUHAN KELUARGA - Alfinatun Ni’mah; Istikharoh Istikharoh; Moh. Iljam (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2022)
The aim of this research is 1) to determine the factors that cause long distance marriages in Losari Village, Rawalo District, Banyumas Regency. 2) to find out the strategies used by husband and wife couples who carry out long-distance marriages in maintaining family integrity in Losari Village, Rawalo District, Banyumas Regency. This research is field research (field research). The nature of this research is qualitative research, namely research that emphasizes the quality or most important things of a good or service. The most important thing is that goods or services are events, phenomena and social phenomena. The results of this research are first, the factors that cause long distance marriages in Losari Village, Rawalo District, Banyumas Regency are economic or work factors. The strategy used by married couples in long distance marriages is to maintain mutual commitment, maintain mutual communication, continue to carry out each other's rights and obligations as husband and wife, and be loyal to their partner.